Electrodeposited TiO2 Film with Mossy Nanostructure for Efficient Compact Layer in Scaffold‐Type Perovskite Solar Cell. Issue 3 (11th January 2018) - Su, Tzu‐Sen; Hsieh, Tsung‐Yu; Wei, Tzu‐Chien
Abstract : A quality compact layer (CL) with a thin and pinhole‐free structure is essential for an efficient perovskite solar cell (PSC). This study offers a new perspective regarding a criterion of a quality CL, namely three‐dimensional interfacial contact. In an examination of the deposition mechanisms, film morphologies, and optical and electronic properties of CLs fabricated using different methods, an electrodeposited (ED) TiO2 CL outperformed other TiO2 CLs. This is not only because of its ultrathin, fully covered morphology but also because of its mossy structure, which provides high shunt resistance and low ohmic resistance in ED‐TiO2 ‐based PSCs. In addition, our results confirm that in scaffold‐type PSCs, the CL provides a charge extraction function in addition to the mesoporous scaffold, which is designed as the main electron transporting layer. Abstract : A three‐dimensional structure of TiO2 compact layer is created by anodic electrodeposition. The fully covered and mossy structural compact layer can provide additional advantages including better charge extraction capability, lower contact resistance, and lower hysteresis behavior than a smooth and pinhole‐free compact layer. This work provides plenty information for interpreting the influence of compact layers in perovskite solar cells.